2020
DOI: 10.1093/nar/gkaa002
|View full text |Cite
|
Sign up to set email alerts
|

tRNA 2′-O-methylation by a duo of TRM7/FTSJ1 proteins modulates small RNA silencing in Drosophila

Abstract: 2′-O-Methylation (Nm) represents one of the most common RNA modifications. Nm affects RNA structure and function with crucial roles in various RNA-mediated processes ranging from RNA silencing, translation, self versus non-self recognition to viral defense mechanisms. Here, we identify two Nm methyltransferases (Nm-MTases) in Drosophila melanogaster (CG7009 and CG5220) as functional orthologs of yeast TRM7 and human FTSJ1. Genetic knockout studies together with MALDI-TOF mass spectrometry and RiboMethSeq mappi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(82 citation statements)
references
References 117 publications
10
72
0
Order By: Relevance
“…In Drosophila it has been recently shown that methylation marks protect tRNAs from cleavage and that aberrant tRFs populations accumulate in methylation mutants: on the one hand, Dnmt2 mutation impairs m 5 C methylation (Schaefer et al, 2010;Durdevic et al, 2013a;Genenncher et al, 2018). On the other hand, dTrm7_34 (CG7009) and dTrm7_32 (CG5220) mutation impairs 2 -O-methylation (Angelova et al, 2020). 2 -O-methylation is one of the most common RNA modifications and consists in the addition of a methyl group to the 2 hydroxyl of the ribose moiety of a nucleoside, being also known as Nm.…”
Section: (Supplementarymentioning
confidence: 99%
See 4 more Smart Citations
“…In Drosophila it has been recently shown that methylation marks protect tRNAs from cleavage and that aberrant tRFs populations accumulate in methylation mutants: on the one hand, Dnmt2 mutation impairs m 5 C methylation (Schaefer et al, 2010;Durdevic et al, 2013a;Genenncher et al, 2018). On the other hand, dTrm7_34 (CG7009) and dTrm7_32 (CG5220) mutation impairs 2 -O-methylation (Angelova et al, 2020). 2 -O-methylation is one of the most common RNA modifications and consists in the addition of a methyl group to the 2 hydroxyl of the ribose moiety of a nucleoside, being also known as Nm.…”
Section: (Supplementarymentioning
confidence: 99%
“…It has been recently shown that Drosophila proteins dTrm7_34 and dTrm7_32 are the functional orthologs of yeast TRM7 (Pintard, 2002) and human FTSJ1 (Guy et al, 2015) respectively, which are involved in 2 -O-methylation of the anticodon loop of several conserved tRNAs substrates (tRNA-Leu, Trp, Phe). Mutations of these tRNAs methyltransferases in Drosophila lead to lifespan reduction, small non-coding RNA pathways dysfunction and increased sensitivity to RNA virus infections, besides specific tRFs accumulation (Angelova et al, 2020).…”
Section: (Supplementarymentioning
confidence: 99%
See 3 more Smart Citations